Physical Activity Behaviour: An Overview of Current and Emergent Theoretical Practices - Duncan S. Buchan; Stewart Ollis; Non E. Thomas; Julien S. Baker (Journal of Obesity)
Physical activity research has been dominated by traditional cognitive rationale paradigms utilized within other domains. Though this approach to physical activity behavior has greatly enhanced our understanding of the key determinants, it has done little to eradicate the health problems we currently face. In order to achieve lasting change though, multilevel interventions may prove effective. Ecological perspectives have been proposed as an effective approach in combating current physical inactivity levels. Nevertheless, this approach is in its infancy and much has still to be learned. The aim of this paper is to provide an overview of the main behavioral models used within the physical activity domain while proposing the need for further models that will embrace the principles presented by ecological and complexity theories.